Bilingualism and Linguistic Politics in Adonara, East Flores - Nancy Lutz (Antropologi Indonesia, 1998)
"...[...] the association of Indonesian with extralocal Power and affiliation, moreover, to speak Indonesian in Adonara is also to deny local roots and affiliations. Perhaps as the population becomes increasingly fluent in Indonesian, these dynamics will become less contentious; through the 1980s and 1990's, however, language choice was still a vehicle for conflicting political stances and affiliations. Nevertheless, as the politics of languages change so too will the languages of politics. From bahasa adat to bahasa protocol, ceremonial language forms in Adonara as throughout Nusa Tenggara Timur will continue to evolve, creating new and dynamic speech forms, like the speech given by Kiwan'ona's Kepala Desa."